TYPES, SYMPTOMS AND TREATMENT METHODS OF CHRONIC SCLERODERMA (SYSTEMIC SCLEROSIS) - Toshpo’latov To’lqin Alyorovich; Aminova Mohinur Normurod qizi, Mingturayev Dilshod Karimovich. Qilichev Jasurbek Fayzullayevich, Qobulov Boburbek Dilshodbek o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
Nowadays, scleroderma is on the rise. This disease is a chronic disease, our article provides information about scleroderma, i.e. what is scleroderma, its symptoms, what processes occur in a sick person, the pathology of the internal organs of the sick patient, i.e. what processes are going on in the organs, changes and teaches to treat it partially.